2008
DOI: 10.1007/s10571-008-9309-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Endoplasmic Reticulum Stress Response After Global Forebrain Ischemia/Reperfusion in Rats: Effect of Neuroprotectant Simvastatin

Abstract: Simvastatin is a cholesterol-lowering agent whose functional significance and neuroprotective mechanism in ischemic brain injury is not yet solved. The purpose of this study is to evaluate the effect of simvastatin on ischemic brain injury. We examined the endoplasmic reticulum stress response (UPR/unfolded protein response), by measuring the mRNA and protein levels of specific genes such as ATF6, GRP78, and XBP1 after 15 min 4-VO ischemia and different times of reperfusion (1, 3, and 24 h). The results from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 45 publications
2
48
0
Order By: Relevance
“…In particular, given that activation of small GTPases such as RAS contributes to about 20% of human cancers, the ability of statins to inhibit GTPases holds the potential for their use as anti-cancer therapeutics (1,32). Another example is the in vivo use of statins to induce the UPR in a rat model where it had neuroprotective effects under ischemic conditions (33). Indeed, induction of the UPR is likely to be protective in several disease contexts, including Parkinson disease (34) and diabetes (35), where misfolded proteins or increased protein production impose a burden on the ER.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, given that activation of small GTPases such as RAS contributes to about 20% of human cancers, the ability of statins to inhibit GTPases holds the potential for their use as anti-cancer therapeutics (1,32). Another example is the in vivo use of statins to induce the UPR in a rat model where it had neuroprotective effects under ischemic conditions (33). Indeed, induction of the UPR is likely to be protective in several disease contexts, including Parkinson disease (34) and diabetes (35), where misfolded proteins or increased protein production impose a burden on the ER.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins translocate to the nucleus, where they induce the expression of genes coding for molecular chaperones and folding enzymes, including GRP78 itself, HERP (homocysteine-inducible, ER-stress inducible protein), GRP94, calnexin and PDI (protein disulphide isomerase) (Kokame et al, 2000;Kokame et al, 2001). An increase in the expression of the grp94, grp78, herp, calnexin and pdi genes was observed after transient ischemia using different models (Aoki et al, 2001;Paschen et al, 2003;Truettner et al, 2009;Urban et al, 2009), and this effect was correlated with a small upregulation of GRP78 and GRP94 protein levels in the hippocampus of rats subjected to the two-vessel occlusion brain ischemia model (Truettner et al, 2009). A significant upregulation of GRP78 protein levels was also observed in the ischemic territory after transient MCAO in mice (Shibata et al, 2003).…”
Section: Endoplasmic Reticulum (Er) Stress In Brain Ischemiamentioning
confidence: 94%
“…On the other hand 6-10-minutes long global ischemia and three days of reperfusion caused death of almost all pyramidal neurons in the same hippocampal area (Coimbra and Wieloch, 1994). Urban et al, (2009) showed a significant increase of XBP1 mRNA level in ischemic phase in comparison to control (about 43% more). These findings are similar to those observed by Paschen (2003a), which showed a marked increase in processed XBP1 mRNA levels using semi-quantitative RT-PCR after focal ischemia.…”
Section: Prophylactic Treatment With Statins: Effect On Ischemic Damagementioning
confidence: 83%
“…As shown by previous studies, the changes of the UPR gene expression induced by transient ischemia occur mostly during the first 24 h (Paschen 2003b) or the first few days after the insult (Qi et al, 2004). In line with this, Urban et al (2009) have decided to measure changes in mRNA and protein levels of GRP78, ATF6, and XBP1 after 15 min of global ischemia and 1, 3, and 24 h reperfusion (UPR reaction). In addition, they have focused their attention on the effect of simvastatin pretreatment on the stress reaction of endoplasmic reticulum induced by ischemic/reperfusion insult.…”
Section: Prophylactic Treatment With Statins: Effect On Ischemic Damagementioning
confidence: 95%
See 1 more Smart Citation